A Critical View of the Uniform Crime Reports - Robison, Sophia M. (1966)
No one would deny that the FBI performs a vital function in investigating, identifying, and tracking down suspects who may endanger the life, liberty, and property of Americans. However, this writer feels that the Uniform Crime Reports published by the FBI should be subjected to a very critical analysis. Of primary concern are the indiscriminate acceptance of the official data by legislators and social science investigators and the doubtful inferences which a frightened public draws from news releases proclaiming that the U.S. is sitting on a seething volcano of crime